Effects of Sugarcane/Peanut Intercropping on Root Exudates and Rhizosphere Soil Nutrient - Xiumei Tang; Lulu Liao; Haining Wu; Jun Xiong; Zhong Li; Zhipeng Huang; Liangqiong He; Jing Jiang; Ruichun Zhong; Zhuqiang Han; Ronghua Tang (Plants, 2024)
Intercropping can enable more efficient resource use and increase yield. Most current studies focus on the correlation between soil nutrients and crop yield under intercropping conditions. However, the mechanisms related to root exudates and soil nutrients remain unclear. Therefore, this study explored the correlation between rhizosphere soil nutrients and root exudates in sugarcane/peanut intercropping. Root extracts, root exudates, rhizosphere soil enzyme activities, and soil nutrients were analyzed and compared in monocultured and intercropped peanut and sugarcane at different growth stages. The root metabolites were annotated using the Kyoto Encyclopedia of Genes and Genomes pathways to further identify the connection between soil nutrients and root exudates. The effects of intercropping differed in peanut and sugarcane at different growth stages, and the difference between podding and pod-filling stages was significant. Intercropping generally had a great effect on peanut; it not only significantly increased the organic acid, soluble sugars, and phenolic acids in root exudates and extracts from peanuts, but also significantly increased rhizosphere soil enzyme activities and soil nutrient levels. Intercropping peanuts promoted fumaric acid secretion from roots and significantly affected the metabolic pathways of alanine, aspartate, and glutamate. Sugarcane/peanut intercropping can increase root exudates and effectively improve soil nutrients. The changes in soil nutrients are closely related to the effects of fumaric acid on alanine, aspartate, and glutamate metabolism.